Financial, governance and environmental determinants of corporate social responsible disclosure. Issue 10 (11th November 2014) - Giannarakis, Grigoris; Konteos, George; Sariannidis, Nikolaos
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the vital determinants on the extent of corporate social responsibility (CSR) disclosure in a US context. The selected variables are CEO duality, the presence of women in the board, greenhouse gas (GHG) emissions, emission reduction initiatives, company's risk premium, financial leverage and industry's profile. Design/methodology/approach – The environmental, social and governance (ESG) disclosure score is used as a proxy for the extent of CSR disclosure calculated by Bloomberg. The influence of plausible variables on the ESG disclosure score and its sub-categories was examined by using the least squares dummy variable model (LSDV) incorporating 100 companies listed on Standard & Poor's 500 Index for the period 2009-2012. Findings – The results show that the emission reduction initiatives and GHG emissions influence positively the extent of ESG score. In addition, slight differences exist concerning the determinants of different types of disclosures. Furthermore, it is illustrated that a company's industrial profile seems to have differences among the extent of the different types of disclosure. Research limitations/implications – The sample of companies is based on the US companies incorporating only large-sized ones. Originality/value – The study extends previous studies with the inclusion of both traditional and innovative determinants of the CSR disclosure in USA taking into account four years of corporate data. A third party rating approach was adopted in order to calculate the extent of CSR disclosure. Finally, both the shareholders' and the investors' attitudes in relation to CSR disclosure are presented.